1993
DOI: 10.1073/pnas.90.14.6586
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell clonal anergy is induced by antigen presentation in the absence of B7 costimulation.

Abstract: The maximal T-cell response to its antigen requires presentation of the antigen by a major histocompatibility complex class II molecule as well as the delivery of one or more costimulatory signals provided by the antigenpresenting cell (APC). Although a number of candidate molecules have been identified that are capable of delivering a costimulatory signal, increasing evidence suggests that one such critical pathway involves the interaction of the T-cell surface antigen CD28 with its ligand B7, expressed on AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
302
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(314 citation statements)
references
References 29 publications
8
302
1
3
Order By: Relevance
“…IL2 is mainly produced by T cells during their activation and enhances their own expansion. 20,21 Production of IL2 is diminished in many patients with cancer due to T cell anergy [45][46][47] and several phase I studies [23][24][25][26]48 have shown that administration of Ad5-IL2 gene-modified tumor cells can induce specific antitumor responses mediated by T cells. Although successful in these studies in solid tumors, Ad5-IL2 is limited in gene therapy of hematopoietic malignancies by its low efficacy of infection and by a high toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…IL2 is mainly produced by T cells during their activation and enhances their own expansion. 20,21 Production of IL2 is diminished in many patients with cancer due to T cell anergy [45][46][47] and several phase I studies [23][24][25][26]48 have shown that administration of Ad5-IL2 gene-modified tumor cells can induce specific antitumor responses mediated by T cells. Although successful in these studies in solid tumors, Ad5-IL2 is limited in gene therapy of hematopoietic malignancies by its low efficacy of infection and by a high toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Both the TCR and CD28 are constitutively expressed by most naïve T cells, enabling them to respond to the antigen being presented [1]. Without costimulation, the signal from the TCR induces the tolerance of T cells to their cognate antigen, instead of being activated [2].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] In contrast, blockade of this pathway results in the induction of antigen-specific unresponsiveness, or anergy, both in vitro and in vivo. 7,8 However, several other T cell-APC interactions can also provide costimulation. One such interaction is mediated by cytotoxic T-lymphocyte antigen-4 (CTLA-4), which is structurally related to CD28, but it inhibits rather than enhances T-cell activation.…”
Section: Introductionmentioning
confidence: 99%